Impact of Hydrotechnical Structures on Hydrological Regime of the Gwda and Drawa Rivers - Kubiak-Wójcicka, Katarzyna; Kornaś, Marika (Quaestiones Geographicae, 2015)
The work attempts to determine the impact of hydrotechnical structures on regimes of rivers. The aim of the article is to compare hydrological regimes of the rivers Gwda and Drawa due to the differences of hydrotechnical works located on both rivers. The Gwda River is heavily managed by hydrotechnical infrastructure. Presently, there are twelve hydropower plants located along the entire length of the river. The Drawa River, on the other hand, has little hydrotechnical infrastructure. Only two hydropower plants are located on the Drawa River. The study of the hydrological regime was carried out on the basis of the analysis of changes of water stages and ice phenomena. River profiles selected for the analysis were located downstream of hydrotechnical works, i.e. hydropower plants. The conclusions were based on the comparative analysis. The impacts were identified as the differences in processes described by the analyzed parameters